2004
DOI: 10.1158/1078-0432.ccr-03-0171
|View full text |Cite
|
Sign up to set email alerts
|

Pretargeted α Emitting Radioimmunotherapy Using 213Bi 1,4,7,10-Tetraazacyclododecane-N,N′,N″,N‴-Tetraacetic Acid-Biotin

Abstract: Purpose: The use of an ␣ emitter for radioimmunotherapy has potential advantages compared with ␤ emitters. When administered systemically optimal targeting of intact antibodies requires >24 h, therefore limiting the use of shortlived ␣ emitters. This study investigated the biodistribution of bismuth-labeled biotin in A431 tumor-bearing mice pretargeted with antibody B3-streptavidin (B3-SA) and examined the therapeutic efficacy of the ␣ emitter, 213Bi-labeled biotin. Experimental Design: Biotinidase-resistant 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Other investigators have reported tumor growth inhibition and prolongation of survival in mice bearing A431 epidermoid carcinomas that were treated with anti-Ley B3 Ab-SA conjugates followed by 213 Bi-labeled DOTA-biotin. 53 Our study demonstrates that systemic therapy with 213 Bi using the PRIT approach can lead to prolonged complete remissions of lymphoma xenografts with minimal toxicities in a preclinical model.Toxicity and pharmacokinetic studies with 225 Ac-Hu195 in mice and cynomologous monkeys and with pretargeted ␣-emitters including 213 Bi and 212 Pb 53,54 suggest that renal tubular damage may be the principal toxicity of this approach. 29,55 Therefore, we evaluated the efficacy of DMPS to reduce nonspecific uptake of 213 Bi in the kidney by providing it in the drinking water.…”
mentioning
confidence: 66%
“…Other investigators have reported tumor growth inhibition and prolongation of survival in mice bearing A431 epidermoid carcinomas that were treated with anti-Ley B3 Ab-SA conjugates followed by 213 Bi-labeled DOTA-biotin. 53 Our study demonstrates that systemic therapy with 213 Bi using the PRIT approach can lead to prolonged complete remissions of lymphoma xenografts with minimal toxicities in a preclinical model.Toxicity and pharmacokinetic studies with 225 Ac-Hu195 in mice and cynomologous monkeys and with pretargeted ␣-emitters including 213 Bi and 212 Pb 53,54 suggest that renal tubular damage may be the principal toxicity of this approach. 29,55 Therefore, we evaluated the efficacy of DMPS to reduce nonspecific uptake of 213 Bi in the kidney by providing it in the drinking water.…”
mentioning
confidence: 66%
“…Renal toxicity was observed in 2 of 10 assessable animals given 900 ACi of the pretargeted 90 Y-peptide whereas other animals given this dose only had mild to moderate histologic changes, indicating that lower doses should be used. Although evidence for some degree of renal toxicity has previously been observed (26,29), other studies have not reported renal damage with doses as high as 1.0 mCi of pretargeted 90 Y-biotin, but these investigations may have been terminated prematurely or evaluated in only a small number of animals. Because the distribution of radionuclides can be monitored easily in patients by external scintigraphy, the risk for renal toxicity can be reduced by the use of dosimetry and with an understanding of radiation dose-response relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, free bismuth-213 leached from unstable ACs is also incorporated to some extent into kidney cells. 12 Radiation nephropathy in mice was observed for 9.25 MBq of 213 Bi-DOTA-biotin 13 and for 10 MBq of 213 Bi-Fab' 14 at six months. Some mild chronic nephropathy was observed for 11.4 MBq of 213 Bi-DOTATOC.…”
Section: Introductionmentioning
confidence: 99%